Preventing diagnostic overshadowing to improve the physical health of people with severe mental illness - Nash, Michael (My University, 2024)
People with severe mental illness (SMI) often have suboptimal physical health and associated outcomes. An important issue for mental health nurses to be aware of is diagnostic overshadowing, which occurs when healthcare professionals misattribute a person’s physical health symptoms to their existing mental illness. This misattribution increases the likelihood of delays in treatment, potentially giving rise to complications that further negatively influence health outcomes. While the causes of diagnostic overshadowing are complex and multifaceted, mental health nurses need to ensure that their practice is not a contributing factor, which requires ongoing self-reflection on their knowledge, skills and attitudes. This article defines diagnostic overshadowing, proposes potential explanations for why it may occur and offers practical strategies to prevent it. Raising awareness of diagnostic overshadowing could help to improve physical health outcomes for people with SMI.
PUBLISHED
Keywords: comorbidity, decision making, discrimination, diversity, mental health, nursing care, patient experience, patients, professional, professional issues, stigma; Health Disparities; Health attitudes and behaviour; Mental health nursing; Nurse Education